Model Pengembangan Strategi Manajemen Terhadap Peningkatan Mutu Pendidikan Di SDN 9 Baru-Baru Tanga - Salmah Salmah; Wahyuni Wahyuni; Ashabul Kahfi (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This study aims to determine the results of developing strategic management in improving the quality of education at SDN 9 Baru-Baru Tanga, which is broken down into several sub-problems: How to develop management strategies to improve the quality of education at SDN 9 Baru-Baru Tanga and How are the results of developing management strategies in improving quality of education at SDN 9 Baru-Baru Tanga? The research method uses qualitative methods, through pedagogic, historical, phenomenological and psychological approaches. Data collection was used through observation, interviews and documentation studies which were carried out entirely by the researcher as the main instrument for obtaining answers and field observations, by bringing cellphones and interview guides as complementary instruments. The data obtained was then carried out by a data reduction process and then the data was presented and tested using data triangulation techniques namely source, method, technique and time triangulation. Furthermore, conclusions are drawn based on the results of the research conducted.